2022
DOI: 10.1186/s12935-022-02786-6
|View full text |Cite
|
Sign up to set email alerts
|

Tiliroside suppresses triple-negative breast cancer as a multifunctional CAXII inhibitor

Abstract: Triple negative breast cancer (TNBC) is an aggressive subtype of breast cancer characterized by poor prognosis, early recurrence, and the lack of durable chemotherapy responses and specific targeted treatments. In this preclinical study, we examines Tiliroside (TS, C30H26O13), as one of the major compounds of Tribulus terrestris L. which has been used as an alternative therapy in clinic practice of breast cancer treatment, for its therapeutic use in TNBC. The association between CAXII expression level and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In addition, CAXIIis have also been found to increase the apoptosis of macrophages, reduce the ratio of macrophages in total CD45+ cells, and increase the ratio of CD8+ T cells in total tumor lymphocytes ( 47 ). Such a result is partly consistent with our previous study in which targeting CAXII can effectively inhibit the development of liver cancer and triple-negative breast cancer cells ( 32 , 49 ). What is noteworthy is that even though CAXII was mainly concentrated on tumor-infiltrating macrophages in the majority of tumor samples, it has also been found that CAXII might be important for the survival and function of M2-subtype macrophages in the tissues of HCC ( 47 ).…”
Section: Effects Of Carbonic Anhydrase XII Inhibitor On Macrophagessupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, CAXIIis have also been found to increase the apoptosis of macrophages, reduce the ratio of macrophages in total CD45+ cells, and increase the ratio of CD8+ T cells in total tumor lymphocytes ( 47 ). Such a result is partly consistent with our previous study in which targeting CAXII can effectively inhibit the development of liver cancer and triple-negative breast cancer cells ( 32 , 49 ). What is noteworthy is that even though CAXII was mainly concentrated on tumor-infiltrating macrophages in the majority of tumor samples, it has also been found that CAXII might be important for the survival and function of M2-subtype macrophages in the tissues of HCC ( 47 ).…”
Section: Effects Of Carbonic Anhydrase XII Inhibitor On Macrophagessupporting
confidence: 93%
“…Evidence has displayed that TS can inhibit the proliferation, colony formation, migration, three-dimensional (3D) organoid formation, and invasive abilities by regulating apoptosis and stemness in HCC cells while having low toxicity to normal cells ( 32 ). The study also found that TS can regulate the tumor microenvironment by modulating the levels of pHi, pHe, and lactate, therefore inhibiting the development of triple-negative breast cells, and act as a multifunctional CAXIIi ( Figure 1 ) ( 49 ).…”
Section: Potential Carbonic Anhydrase XII Inhibitorsmentioning
confidence: 92%
“…Tiliroside is an example of a flavonoid with potential for anti-cancer therapy [12][13][14][15][16]. Among others, it revealed its anti-cancer properties by acting as a CAXII inhibitor in liver cancer [12] and by reducing the E2F/caspase-3 axis in breast cancer cell carcinoma [13].…”
Section: Discussionmentioning
confidence: 99%
“…Tiliroside is an example of a flavonoid with potential for anti-cancer therapy [12][13][14][15][16]. Among others, it revealed its anti-cancer properties by acting as a CAXII inhibitor in liver cancer [12] and by reducing the E2F/caspase-3 axis in breast cancer cell carcinoma [13]. Recently we have demonstrated the anti-tumor potential of tiliroside in AGS gastric cancer cells by affecting MUC1 and some specific glycoforms involved in cancer development [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation